Centrosome amplification is a frequent event in circulating tumor cells from subjects with metastatic breast cancer - Singh, Ashok; Denu, Ryan A.; Wolfe, Serena K.; Sperger, Jamie M.; Schehr, Jennifer; Witkowsky, Tessa; Esbona, Karla; Chappell, Richard J.; Weaver, Beth A.; Burkard, Mark E.; Lang, Joshua M. (Molecular oncology, 2020)
Centrosome amplification (CA) is a common phenomenon in cancer, promotes genomic stability and cancer evolution, and has been reported to promote metastasis. CA promotes a stochastic gain/loss of chromosomes during cell division, known as chromosomal instability (CIN). However, it is unclear whether CA is present in circulating tumor cells (CTCs), the seeds for metastasis. Here, we surveyed CA in CTCs from human subjects with metastatic breast cancer. CTCs were captured by CD45 exclusion and selection of EpCAM‐positive cells using an exclusion‐based sample preparation technology platform known as VERSA (versatile exclusion‐based rare sample analysis). Centriole amplification (centrin foci> 4) is the definitive assay for CA. However, determination of centrin foci is technically challenging and incompatible with automated analysis. To test if the more technically accessible centrosome marker pericentrin could serve as a surrogate for centriole amplification in CTCs, cells were stained with pericentrin and centrin antibodies to evaluate CA. This assay was first validated using breast cancer cell lines and a nontransformed epithelial cell line model of inducible CA, then translated to CTCs. Pericentrin area and pericentrin area x intensity correlate well with centrin foci, validating pericentrin as a surrogate marker of CA. CA is found in CTCs from 75% of subjects, with variability in the percentage and extent of CA in individual circulating cells in a given subject, similar to the variability previously seen in primary tumors and cell lines. In summary, we created, validated, and implemented a novel method to assess CA in CTCs from subjects with metastatic breast cancer. Such an assay will be useful for longitudinal monitoring of CA in cancer patients and in prospective clinical trials for assessing the impact of CA on response to therapy. Circulating tumor cells (CTCs) are a rare population of cancer cells released into peripheral circulation from primary and metastatic cancer sites. Centrosome amplification (CA) has been reported in virtually all human cancers and has been shown to make cells more invasive. In this study, we develop an assay to detect CA in CTCs. We find that CA is prevalent in CTCs from subjects with metastatic breast cancer.